2022
DOI: 10.3389/fonc.2022.952847
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the cervical lesion region in colposcopic images based on deep learning

Abstract: BackgroundColposcopy is an important method in the diagnosis of cervical lesions. However, experienced colposcopists are lacking at present, and the training cycle is long. Therefore, the artificial intelligence-based colposcopy-assisted examination has great prospects. In this paper, a cervical lesion segmentation model (CLS-Model) was proposed for cervical lesion region segmentation from colposcopic post-acetic-acid images and accurate segmentation results could provide a good foundation for further research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Cervical cancer is easily preventable with early screening and diagnosis. It is acknowledged that the bulk of deep learning-based artificial intelligence has been used in cytology, colposcopy, and DNA methylation research for cervical intraepithelial lesions [28][29][30]. Jian et al [31] showed that machine learning can identify methylation signals associated with the development of cervical cancer at qualitative and quantitative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is easily preventable with early screening and diagnosis. It is acknowledged that the bulk of deep learning-based artificial intelligence has been used in cytology, colposcopy, and DNA methylation research for cervical intraepithelial lesions [28][29][30]. Jian et al [31] showed that machine learning can identify methylation signals associated with the development of cervical cancer at qualitative and quantitative levels.…”
Section: Discussionmentioning
confidence: 99%
“…The Region of Interest’s (ROI) imaging signals can be filtered. In terms of image segmentation, the consensus typically acknowledges that image segmentation divides an image into smaller regions or objects based on its elements and this is dependent on the tissue of interest [ 39 , 40 ]. The precision of the image segmentation phase will heavily influence the efficacy and efficiency of the subsequent stages in image processing [ 41 ].…”
Section: Radiogenomics and Its Use In Precision Medicinementioning
confidence: 99%
“…Promising solutions to this problem are offered by colposcopy-assisted examinations using artificial intelligence. A cervical lesion segmentation model (CLS-Model) was proposed by Yu et al [ 12 ] for the segmentation of the cervical lesion region from colposcopic post-acetic-acid images. According to this paper, precise segmentation results might offer a strong starting point for future studies on lesion identification and biopsy site choices.…”
Section: Literature Reviewmentioning
confidence: 99%